Epstein-Barr virus predominance and immunological abnormalities in oral squamous cell carcinoma - Ahmed Talib Ghadhban; Marwa Mohammed Ali Jassim; Majid Mohammed Mahmood (University Library System, University of Pittsburgh, 2023)
BACKGROUND: Both benign and harmful head and neck disorders have been associated with the Epstein-Barr virus (EBV). Many studies have connected EBV to oral squamous cell carcinoma (OSCC). Oral squamous cell carcinoma is the most prevalent type of cancer. Fresh tissue samples from patients with OSCC were tested for the presence of Epstein-Barr virus. OBJECTIVE: To determine the frequency of EBV and IL10 expression in OSCC patients. MATERIALS AND METHODS: Fifty individuals with OSCC and 25 with clinically healthy oral mucosa were studied. In situ hybridization was used for the detection of EBV. Serum IL-10 levels were also evaluated in patients and controls using a human IL-10 ELISA Kit. RESULTS: EBV was detected in 4 healthy patients, 6 with moderately differentiated OSCC, 10 with poorly differentiated OSCC, and 19 with undifferentiated OSCC. These differences were statistically significant (p<0.05). IL-10 expression was more common in OSCC diagnostic groups than healthy controls, and the difference in blood IL-10 levels between patients and controls was statistically significant (p<0.01). CONCLUSION: The prevalence of EBV in OSCC suggests its possible role in oral cavity malignancy. On the other hand, IL-10 is expressed at higher levels in OSCC biopsies; such elevated concentrations may promote viral spread.